2019
DOI: 10.1021/acsphotonics.8b01672
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of an Inorganic Barrier Layer as a Method of Improving the Performance of Quantum Dot Light-Emitting Diodes

Abstract: Quantum dot light-emitting diodes (QLEDs) are expected to be the basis of next-generation displays and have consequently been extensively investigated with the aim of commercialization. Herein, QLED brightness, efficiency, and lifetime are significantly improved by insertion of an Al2O3 barrier layer via atomic layer deposition (ALD), which effectively suppresses the etching reaction with poly­(3,4-ethylenedioxythiophene):polystyrenesulfonate and prevents metal ion diffusion from indium tin oxide (ITO) into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 30 publications
(54 reference statements)
1
29
0
Order By: Relevance
“…All devices display nearly saturated colors with the coordinate points approaching the boundary. [18] Notably, comparing with QLEDs prepared by solution processes previously reported, [6,[19][20][21][22][23] we demonstrated a feasible all-solution approach for achieving large-area high-performance QLEDs (Figure 5 i).…”
Section: Angewandte Chemiementioning
confidence: 55%
“…All devices display nearly saturated colors with the coordinate points approaching the boundary. [18] Notably, comparing with QLEDs prepared by solution processes previously reported, [6,[19][20][21][22][23] we demonstrated a feasible all-solution approach for achieving large-area high-performance QLEDs (Figure 5 i).…”
Section: Angewandte Chemiementioning
confidence: 55%
“…The use of ALD Al 2 O 3 has already been proven to be efficient as a diffusion barrier layer to prevent diffusion of species or charges in photonic devices. [ 40,41 ] In Figure 4b, the subthreshold currents are significantly reduced by more than 2 orders of magnitude thanks to the oxide. This phenomenon was observed on devices fabricated in the same batch of experiments, and was found to be reproducible by measuring several devices.…”
Section: Resultsmentioning
confidence: 99%
“…At the end, prospects of ALD applications on QDs based devices are discussed from the aspects of ALD materials, process parameters, in-situ characterization and device simulations. 86,88 CdSe/ZnS 61,66,77,87 ZnCdSSe/ZnS 68 CdSe@ZnS/ZnS 63 CdSe/CdS/ZnS 69,71 PbS 56,67,72,78,81,[83][84][85]89 PbSe 55,57,74,79,80 APbX3 60,65,70,75 Sphere 65 Film 57,58,66,69,70,73,74,77 FET 55,62,76,[78][79][80]83,86,88 Solar cell 56,82,84,85 Photodetector 67,…”
Section: (Iii) and (Iv)mentioning
confidence: 99%
“…The systematic study showed that an optimized 2 nm ALD-TiO 2 layer under 200 °C could promote solar cell efficiency by balancing the charge transfer. Additionally, Choi et al employed an inorganic barrier layer fabricated by ALD to improve the performance of QLED in both maximal luminance and current efficiency 61 . The Al 2 O 3 barrier layer could hinder the etching reaction with PEDOT:PSS and prevent metal ion diffusion from indium tin oxide into the emission layer sufficiently as shown in Fig.…”
Section: Interface Engineeringmentioning
confidence: 99%